2011
DOI: 10.1002/jsfa.4422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest time on seed oil and protein contents and compositions in the oleaginous gourd Lagenaria siceraria (Molina) Standl

Abstract: Both cultivars of L. siceraria should be harvested at 50 DAFS owing to the good nutritional properties of their seeds and oils. However, to obtain best-quality proteins, round and oval berry cultivars should be harvested at 30 DAFS and CPW respectively. The results of this study will be useful in reducing the production time of fruits and improving the nutritional quality of their seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…As an oleaginous crop, bottle gourd (L. siceraria) is an understudied plant whose kernel is about 50.3% (weight per weight) oil [9]. The mature kernels of L. siceraria contain four major triacylglycerols (TAGs) which include trilinolein (LLL), palmitoyldilinoleoyl glycerol (PLL), oleoyldilinoleoyl glycerol (OLL) and dioleoyllinoleoyl glycerol (OOL) [10].…”
Section: Introductionmentioning
confidence: 99%
“…As an oleaginous crop, bottle gourd (L. siceraria) is an understudied plant whose kernel is about 50.3% (weight per weight) oil [9]. The mature kernels of L. siceraria contain four major triacylglycerols (TAGs) which include trilinolein (LLL), palmitoyldilinoleoyl glycerol (PLL), oleoyldilinoleoyl glycerol (OLL) and dioleoyllinoleoyl glycerol (OOL) [10].…”
Section: Introductionmentioning
confidence: 99%
“…LSO was less stable than peanut oil, which, in turn, was less stable than palm and olive oils, respectively. However, the physicochemical properties of this oil (Loukou et al . 2011) meet the standards of Codex Alimentarius for edible oils.…”
Section: Discussionmentioning
confidence: 99%
“…LSO was less stable than peanut oil, which, in turn, was less stable than palm and olive oils, respectively. However, the physicochemical properties of this oil (Loukou et al 2011) meet the standards of Codex Alimentarius for edible oils. According to Matthäus et al (2010), the roasting process had a positive effect on storage stability of the resulting oils.…”
Section: Comparison Of Oxidative Stability Of Lagenaria Siceraria Andmentioning
confidence: 94%
“…Cucurbits are among the most economically important vegetables in the world. In West Africa, there are at least five Cucurbitaceae species regularly cultivated by the populations [6]. These plant species are of significant socio-economic importance in the life of sub-Saharan people, especially in Côte d'Ivoire where they are source of small-scale livelihood for female farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Locally spelled ''pistaches'', the cucurbit kernels are usually processed into soups, which are very prized for home consumption and during festivities [7]. Previous studies have shown the nutritional interests in some cucurbit kernels [6,8,9]. They are rich source of proteins and lipids, and could therefore be an asset in fortification programs, therefore increasing their use and valorization.…”
Section: Introductionmentioning
confidence: 99%